Communication Management for the UGJ Tancap Qris Event Regarding Literacy in Digital Payment Systems - Tamamala, Ananda Farhan; Khaerudin Imawan; Novicky Alban Adiputra (Jurnal Bisnis dan Komunikasi Digital, 2026)
The development of digital payment systems using the Indonesian Standard Quick Response Code (QRIS) calls for improved digital literacy, particularly among college students. One of the efforts undertaken is through event-based outreach activities, such as the UGJ TANCAP QRIS event organized by the Indonesian New Generation (GENBI) chapter at Swadaya Gunung Jati University (UGJ) in Cirebon. This study aims to analyze the application of communication management in organizing the event and its impact on improving students’ digital payment system literacy. This study uses a qualitative approach with a descriptive mode. Data were collected through in-depth interviews with GENBI executives, the organizing committee, and event participants, as well as supporting documentation. Data analysis was conducted using thematic analysis. The results indicate that communication management in the UGJ TANCAP QRIS event was implemented through four main stages: planning, organizing, execution, and evaluation of communication. Clear message planning, an organized communication structure, a communicative and interactive communication style, and post-event evaluation positively contributed to the effectiveness of information delivery. The research findings also indicate an increase in students’ understanding and interest in the use of QRIS after participating in the activity. This study concludes that well-planned and coordinated communication management plays a crucial role in supporting the success of digital payment system outreach activities within the university environment.